Patient safety culture in Portuguese primary care: validation of the Portuguese version of the Medical Office Survey - Eiras, Margarida (2019)
Background: Assessing patient safety culture is a strategic priority worldwide, and Portugal is no exception. Objective: It is the objective of this work to translate, adapt, validate, and analyze the reliability of the Medical Office Survey on Patient Safety Culture in Portuguese Primary Health Care (MOSPSC). Methods: The methodology adopted focused on transcultural translation and adaptation using the Translation Guidelines for the Agency for Healthcare Research and Quality (AHRQ) surveys on Patient Safety Culture, and reliability was conducted using Cronbach’s α and average inter-item correlation. Exploratory factor analysis and confirmatory factor analysis were performed to investigate the observed data that fit the dimensional structure proposed in the AHRQ Portuguese version. Results: The initial sample (n = 7299) was submitted to missing value analysis, obtaining a final sample of 4304 surveys. With exploratory factor analysis, it was obtained a structure with eight composites, one item was removed, and several items moved to other composites. With confirmatory factor analysis, one composite was removed. For both proposed model structures, good results were achieved for the goodness of fit indices. Conclusions: The Portuguese version of the MOSPSC resulted in nine composites with good reliability and construct validity.